Development and Assessment of Nano-Technologies for Cancer Treatment: Cytotoxicity and Hyperthermia Laboratory Studies. (2nd January 2020) - Medina-Ramírez, Iliana E.; Díaz de León Olmos, María Alejandra; Muñoz Ortega, Martín Humberto; Zapien, Juan Antonio; Betancourt, Israel; Santoyo-Elvira, Nathaly
Abstract: Cancer treatment by magnetic hyperthermia offers numerous advantages, but for practical applications many variables still need to be adjusted before developing a controlled and reproducible cancer treatment that is bio-compatible (non-damaging) to healthy cells. In this work, Fe3 O4 and CoFe2 O4 were synthesized and systematically studied for the development of efficient therapeutic agents for applications in hyperthermia. The biocompatibility of the materials was further evaluated using HepG2 cells as biological model. Colorimetric and microscopic techniques were used to evaluate the interaction of magnetic nano-materials (MNMs) and HepG2 cells. Finally, the behavior of MNMs was evaluated under the influence of an alternating magnetic field (AMF), observing a more efficient temperature increment for CoFe2 O4, a desirable behavior for biomedical applications since lower doses and shorter expositions to alternating magnetic field might be required. Graphical Abstract: